The Effect of Bank Fundamentals, Profit-Loss Sharing Financing, and Covid-19 on the NPF of Islamic Commercial Banks in Indonesia - Fitrah, Jauharil; Widarjono, Agus (Mutanaqishah: Journal of Islamic Banking, 2024)
This study analyzes the influence of bank fundamentals, profit-sharing financing, and Covid-19 on financing default as measured by non-performing financing (NPF) in Islamic commercial banks. The Islamic commercial banks studied were 12 banks in the 2014-2022 period with quarterly data and unbalanced panel data. The estimation method used is the panel regression. The results show that the bank's strong fundamentals, namely bank size, bank capital, and profitability have a negative effect on NPF. Profit-sharing financing, namely Mudharabah, and Musharakah, has a positive effect on NPF. Meanwhile, the stability of banks, bank efficiency, and Covid had no effect on NPF. There are several important policy implications of these findings. First, banks must have strong fundamentals to be able to minimize NPF. Second, profit-sharing financing must be followed by good monitoring so it can reduce NPF.